Pelatihan Membuat Sediaan Masker Gel “peel off “ Dengan Bahan Alam Daun Kelor Sebagai Kosmetik Untuk Mencegah Penuaan Dini Pada Kulit muka - Jumain Jumain; Asmawati Asmawati (Jurusan Farmasi Politeknik Kesehatan Makassar, 2022)
Today the role of family members (mothers) in increasing income is still very small, housewives can help support family income, although now many have jobs outside the home, but many more stay at home, including young girls who drop out of school . Various skill activities that can be done by housewives and young women to increase family income, including making products made from raw materials that are cheap and easy to obtain and easy to produce. The results of the study of fresh Moringa leaves showed that the antioxidant power was 7 times stronger than Vitamin C. Rizkayanti's research, 2017 showed that the antioxidant activity of Moringa leaf extract IC50 = 22.18 bpj in the category of very strong antioxidant activity. Based on this, the community service team tried to apply it, so that Moringa can be used as a raw material for cosmetic products, namely